Ground Water Table under Different Land Uses - Nur Wakhid; Siti Nur Zakiah (Center for Journal Management and Publication, 2018)
Fires in Indonesia tropical peatlands are always associated with peatland conversion. Land use change usually occurs from secondary or primary forest to agricultural land or plantation. However, land use change in Indonesia is inevitable because high demand of land for food supply. Peatlands which are usually associated with wetlands, become dry due to drainage during land clearing and plant growth process. Therefore, the relationship between ground water level (GWL) and fires on tropical peatlands is close. The research objective is to analyze the level of fire vulnerability on peatlands based on the GWL fluctuation under different land uses. GWL measurement was conducted manually every week from February to December 2014 in the field and ditch on three different land uses. Automatic water level measurement tool also conducted from March to December 2014, but only on the field. GWL fluctuation both on ditch and field followed the variation of precipitation. GWL fluctuation under different land uses also significantly different, and automatically results different fire vulnerability.